L’Amazonie péruvienne contemporaine au miroir de sa littérature : « Sélection Loreto 2006 » - Catherine Heymann (Caravelle)
In 2006, at the end of a contest, Loreto’s Regional Government (Peru), published a selection of contemporary authors, who where born or lived in the Amazon basin. Integrated into a strategy of regional development, this cultural politics aimed to bring national and worldwide fame to the Amazonian writers, especially to those from the Loreto Department. After reminding the conditions which permitted the emergence of a regional literature, which is barely one hundred years old, this reflection concerns the self representation shown in the seventeen titles selected.